The Relationship Between Food Appearance And Taste With The Acceptability Of Soft Food Menus In Inpatient Hospital Patients - Normansjah, Ulfah Tivriana; Lestari, Dwi Ayu; Barokah, Falah Indriawati (Sean Institute, 2024)
Acceptability is a measure of satisfaction with food and an individual's ability to finish the food served. Eating habits are one of the internal factors affecting food acceptability, while food appearance and taste are external factors. The purpose of this study is to determine the relationship between food appearance and taste with the acceptability of soft foods in inpatients at Pertamina Balikpapan Hospital. This observational study uses a cross-sectional method. The sample was determined using a systematic accidental sampling method and calculated using Slovin's formula, resulting in a sample size of 60 respondents. Data collection was conducted through interviews and questionnaires. Bivariate statistical analysis in this study used the Chi-square test, yielding p=0,008 for food appearance and acceptability, and p=0,122 for food taste and acceptability. The conclusion is that there is no significant relationship between food appearance and acceptability (p=0,008) and no significant relationship between food taste and acceptability (p=0,122). The results indicate that there is no correlation between food appearance and taste with patient acceptability because patients have been educated on the importance of finishing the food served in the hospital to support the healing process.